Tumour Debulking for Esophageal Cancer - Thermal Modalities - David Fleischer (Canadian Journal of Gastroenterology)
Esophageal cancer usually is discovered at a late stage and curative therapy seldom is possible. The prognosis is poor and most therapy is palliative. Endoscopic therapy commonly is employed; two common treatments involve thermal modalities. The Nd:YAG laser has been employed for 10 years and is effective in relieving obstruction in approximately 90% of cases. Re-ohstruction usually occurs in two to three months and repeat treatment may be necessary. Limitations to laser use include the fact that equipment is expensive and there are technical restrictions. An alternative thermal modality is the bipolar coagulation tumour probe which employs bipolar electrocoagulation. It is less expensive and, if the tumour is circumferential, tends to be easier to use. (It should not be used if the cancer is noncircumferential.) The advantages and limitations of each modality are addressed.